Preliminary experience and learning curve of endoscopic nipple-areolar-complex sparing total mastectomy: A single-center retrospective study. - Da Young Yu; Tae Yul Lee; Duk Woo Kim; Young Woo Chang; Gil Soo Son; Hye Yoon Lee (PLoS ONE)
Background In this study, the preliminary experience of endoscopic nipple-areolar-complex (NAC) sparing total mastectomy were analyzed and reported. Methods The medical records of the patients who underwent Endoscopic NAC sparing total mastectomy from November 2019 to June 2022 in a single institute were collected and analyzed. The medical records of their clinicopathologic characteristics, perioperative parameters, postoperative complications, oncologic results were collected retrospectively. The learning curve was evaluated using univariable and multivariable analyses and analyzed using the CUSUM method. Results A total of 56 surgeries from 53 patients were analyzed. The mean total operation time was 272.50±66.74 minutes while mean oncologic mastectomy was 155.61±43.21 minutes. The mean postoperative hospital days were 9.85±4.70 days. In CUSUM analysis, the cases needed to decrease operation time were 10th. The overall complication rate related to implant was 15.09%. There were one locoregional recurrence patient and one distant metastasis and mortality patient observed during median follow-up of 19.12±12.01 months. Conclusion According to our preliminary study, endoscopic NAC sparing total mastectomy is a safe procedure, and the operation time can be reduced with accumulated surgical experience.